Understanding and Using English Non-Finite Forms - (:unkn) unknown (My University, 2026)
This textbook contains rules and a set of exercises on the grammar of modern English, aimed at mastering the features of using non-finite verb forms: the participle, the gerund, the infinitive. The exercises are supplemented with examples of their implementation and correlate with the corresponding grammatical commentary-reference. The collection can also be used for self-testing of the material studied or for current or final control by the teacher. The textbook is intended for 2nd-year students of the Faculty of Foreign Languages studying English as the 1st foreign language and 3rd-year students studying English as the 2nd foreign language.